Pengaruh Tingkat Financial Distress dan Ukuran Perusahaan Terhadap Konservatisme Akutansi Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 - Mohamad Soedarman (STIE Malangkucecwara, 2017)
This study aimed to investigate the effect of financial difficulties and the level of company size on the level of accounting conservatism. In determining the condition of financial difficulties researchers used financial ratio analysis that profit margin ratio and financial leverage. As for the size of the company using the number of shares outstanding. This study refers to the results of research conducted by Luciana Spicca (2003). Eko Widodo (2005), Nathania Pramudhita (2012), and Ike Restu Prahara (2014). Variables used in this research is the profit margin, financial leverage, company size, and accounting conservatism. The population in this study is from four mining companies mining subsectors listed in the Indonesia Stock Exchange in 2015. The sample in this study using purposive sampling method. Then from the criteria set elect 16 of the 41 companies in the sample. The results using multiple linear regression showed that the profit margin ratio is not striving to accounting conservatism with a probability value of 0.077. Financial leverage has no effect on accounting conservatism with a probability value of 0.143. Firm's size has no effect on accounting conservatism with a probability value of 0.324. Simultaneously three variables affect the accounting conservatism with probability value 0,000. The results of this study concluded that the greater the value of the financial distress ratio and size of the company's simultaneously, then anticipate the company to conservative measures will be even greater.